Conducting a FIMA lifesaver course in the COVID-19 setting by IMAM in Malaysia - Abdul Salim, Noor Hafizah; Abdul Rashid, Aneesa; Md Pauzi, Ahmad Luqman; Isa, Mohd Hisham (Federation of Islamic Medical Associations (FIMA), 2022)
Every year, the Federation of Islamic Medical Association (FIMA) conducts a basic life support (BLS) course for the public, not just in one, but in several countries. It is held in mosques as a method of raising awareness on the importance of BLS among the public, apart from highlighting the function of a mosque as a place of obtaining knowledge. Traditionally, it was conducted as face-to-face training. However, with the 2019 novel coronavirus pandemic, the training was changed to a hybrid method to balance between the needs to teach BLS skills to the public and the necessity of avoiding the spread of infection. This article discussed the Islamic Medical Association of Malaysia (IMAM)’s experience in organizing a mass BLS course for public in the midst of the COVID-19 pandemic while utilising a small mosque as a hub of learning.